Comparative study of the chemical composition of the essential oil of the Lasiocephalus longepenicillatus (Schultz-Bip. ex Sandw.) Cuatrec. (Senecio longepenicillatus) in two seasons of the year - Rondón, María; Morales, Antonio; Buitrago, Diolimar; Rojas, Janne; Gualtieri, María (Ciencia, 1970)
The essential oil of the aerial parts of Lasiocephalus longepenicillatus, was analyzed by CG/EM. A quantitative difference on the chemical composition of the oil was observed between the two botanical samples collected in two different climatic seasons, the dry and rainy seasons. The main components reported for the dry season were germacrene-D (37.79%); a-pinene (26.36%) and a-humulene (12.29%), while the major components observed in the rainy season were a-humulene (33.54%), a- pinene (19.33%) and germacrene-D (17.82%).